La «narrativización» del discurso y el «efecto omnisciente» en no ficción periodística - Saavedra Vergara, Gonzalo (Caplletra. Revista Internacional de Filologia, 2000)
This article shows how the narrator can tell more than what the journalistic nonfiction orthodoxy dictates. By way of narrating a source’s speech, the narrator can report states of consciousness –i.e., feelings, thoughts, perceptions– as it happens in novels that have what is commonly known as omniscient narrators. Although this has never been studied thoroughly, it is a frequent practice in successful nonfiction texts.